(untitled) (diségno, 2022)
The symposium REAACH-ID (Representation for Enhancement and management through Augmented reality and Artificial intelligence: Cultural Heritage and Innovative Design), was held in webinar mode also in its second edition. The virtual events, imposed by the pandemic, have now amply demonstrated the possibility of creating a place for dialogue that overcomes spatial distances. [read more]